The brilliant history of color in art - Finlay, Victoria (J. Paul Getty Museum, 2014)
"Journey from the Ice Age to the Digital Age with a surprising cast of characters on this worldwide tour of color in art. Students will discover the strange, intriguing, and humorous stories of their favorite colors, the science behind them, and how they forever changed the courses of art and history. Big questions will pique your students' curiosity: Why is the sky blue? Why are there seven colors in the rainbow? What is art, anyway? The Brilliant History of Color in Art is also a treasure trove of world art, from cave paintings to Roman treasures and Chinese dragon scrolls; to works by Titian and Michelangelo, Monet and Kandinsky, Rothko and Hockney; to contemporary sculpture and graffiti art. Many of the book's 166 spectacular images are from the collections of the J. Paul Getty Museum."--Publisher's description